010 The melbourne mobile stroke unit substantially improves thrombolysis times and pre-hospital triage. Issue 6 (24th May 2018) - Zhao, Henry; Coote, Skye; Pesavento, Lauren; Langenberg, Francesca; Desmond, Patricia; Easton, Damien; Bent, Lindsay; Foster, Shane; Stephenson, Michael; Smith, Karen; Bernard, Stephen; Bladin, Christopher; et al.
Abstract : Introduction: The Melbourne mobile stroke unit (MSU) project is the first Australian pre-hospital stroke service that delivers on-scene imaging, treatment and triage. The MSU vehicle consists of a Mercedes Sprinter-5 chassis with on-board CereTom 8-slice portable CT scanner and telemedicine capabilities. On-board crew consists of a neurologist/telemedicine, nurse, radiographer and two paramedics (advanced-life-support and mobile-intensive-care). The MSU service is co-dispatched within 20 km of Royal Melbourne Hospital. We describe the service activity since project launch. Methods: Data are sourced from the Melbourne MSU registry, an ongoing prospectively collected database of all MSU dispatched cases since November 2017. Results: In the first 50 operational days, there were a total of n=255 dispatches (5.1/day), of which 47% of patients received on-scene attendance. On-scene CT was performed on 52% of all attendances. Of n=29 suspected ischaemic stroke cases<6 hours of symptom onset (24% of attended), n=10 (34%) received pre-hospital thrombolysis and n=6 (21%) were directed for endovascular thrombectomy. 30% of patients were thrombolysed within 90 min of symptom onset. A total of n=7 (14% of all stroke) patients were recommended to bypass the closest hospital to a specialist centre for endovascular, neurosurgical or other services. The median scene-to-thrombolysis time of 36.5 min was substantially better than Australian in-hospital averages and represented an estimated 30–45 min time saving compared to in-hospital treatment. Discussion: The Melbourne MSU project shows that pre-hospital diagnosis and treatment of stroke patients is feasible and associated with substantial time saving in providing acute stroke treatment and triage. Future research will focus on optimising MSU dispatch and cost-effectiveness analysis.